Top-down approach towards graphene : synthesis and electrochemistry - Chua, Chun Kiang (2013)
Graphene is widely recognized for its unique structural, physical and electronic properties that can be exploited for electrochemical applications. However, its potential application as an electrochemical material is currently impeded by the lack of methods to synthesize graphene in relatively high quality and large quantities. Consequently, this project has focused on investigating methods for graphene synthesis via the top-down approach i.e. the oxidation of graphite to graphite oxide followed by reduction to graphene. Analysis of the various oxidation methods revealed permanganate oxidants to be the most efficient. Five established reduction approaches were demonstrated for the first time to be useful for the conversion of graphene oxide to graphene. These reduction methods offer control over the extent of reduction, production of commercially viable graphene, and restoration of the sp2 carbon network of reduced graphene. In addition, graphene oxide was successfully introduced as an electroactive label for the detection of single nucleotide polymorphism, demonstrating its potential application for biosensing. Furthermore, graphene materials were found to enhance the electrochemical detection resolutions for catechol and dopamine compounds in a lab-on-a-chip detection platform. The improved methods and demonstrated applications would serve as a useful platform for future studies on the synthesis and usage of graphene materials.